Current Status and Future Prospects of TROP-2 ADCs in Lung Cancer Treatment - Li M; Jin M; Peng H; Wang H; Shen Q; Zhang L (Dove Medical Press, 2024)
Mingyi Li,1,* Meng Jin,2,* Hao Peng,3 Haitao Wang,1 Qian Shen,2 Lei Zhang1,4 1Department of Pulmonary and Critical Care Medicine, NHC Key Laboratory of Respiratory Diseases, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of China; 2Department of Oncology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of China; 3Department of Urology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430030, People's Republic of China; 4Xianning Medical College, Hubei University of Science & Technology, Xianning, Hubei, 437000, People's Republic of China*These authors contributed equally to this workCorrespondence: Lei Zhang, Department of Pulmonary and Critical Care Medicine, NHC Key Laboratory of Respiratory Diseases, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People's Republic of China, Email zhl930223@qq.com Qian Shen, Department of Oncology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People's Republic of China, Email shenqianoncology@163.comAbstract: Lung cancer is the leading cause of mortality worldwide, and non-small cell lung cancer accounts for the majority of lung cancer cases. Chemotherapy and radiotherapy constitute the mainstays of lung cancer treatment; however, their associated side effects involving the kidneys, nervous system, gastrointestinal tract, and liver further add to dismal outcomes. The advent of antibody‒drug conjugates (ADCs) could change this situation. Trophoblast surface antigen 2 (TROP-2), a human trophoblast surface antigen, is a tumor-associated antigen that is expressed at low levels in normal tissues and is overexpressed in a variety of malignant tumors. The differential expression of the TROP-2 protein in a variety of tumors makes tumor immunotherapy with ADCs targeting TROP-2 a promising approach. Previous studies have shown that the expression of TROP-2 is related to the prognosis of patients with lung cancer and that TROP-2 expression is different across different histological types; however, research on TROP-2 and TROP-2 ADCs in patients with lung cancer is not comprehensive. The aims of this study were to review the mechanism of action and clinical efficacy of TROP-2 and related drugs in the treatment of lung cancer, to elucidate the prognostic value of TROP-2 in lung cancer, and to discuss the future prospects of TROP-2 ADCs to provide a reference for the precise treatment of lung cancer.Keywords: TROP-2, antibody‒drug conjugates, lung cancer